Air‐Stable, Lead‐Free Zero‐Dimensional Mixed Bismuth‐Antimony Perovskite Single Crystals with Ultra‐broadband Emission. Issue 9 (7th February 2019) - Zhang, Ruiling; Mao, Xin; Yang, Yang; Yang, Songqiu; Zhao, Wenyuan; Wumaier, Tuerdi; Wei, Donghui; Deng, Weiqiao; Han, Keli
Abstract: Lead‐free zero‐dimensional (0D) organic‐inorganic metal halide perovskites have recently attracted increasing attention for their excellent photoluminescence properties and chemical stability. Here, we report the synthesis and characterization of an air‐stable 0D mixed metal halide perovskite (C8 NH12 )4 Bi0.57 Sb0.43 Br7 ⋅H2 O, in which individual [BiBr6 ] 3− and [SbBr6 ] 3− octahedral units are completely isolated and surrounded by the large organic cation C8 H12 N + . Upon photoexcitation, the bulk crystals exhibit ultra‐broadband emission ranging from 400 to 850 nm, which originates from both free excitons and self‐trapped excitons. This is the first example of 0D perovskites with broadband emission spanning the entire visible spectrum. In addition, (C8 NH12 )4 Bi0.57 Sb0.43 Br7 ⋅H2 O exhibits excellent humidity and light stability. These findings present a new direction towards the design of environmentally‐friendly, high‐performance 0D perovskite light emitters. Abstract : Fully visible : An air‐stable, zero‐dimensional (0D) organic‐inorganic mixed Bi–Sb halide perovskite (C8 H12 N)4 Bi0.57 Sb0.43 Br7 ⋅H2 O, in which individual [BiBr6 ] 3− and [SbBr6 ] 3− octahedrons are completely isolated and surrounded by the large organic cation C8 H12 N + is reported. This is the first example of 0D perovskites with broadband emission spanning the entire visible spectrum.